Mitogenomics of historical type specimens clarifies the taxonomy of Ethiopian Ptychadena Boulenger, 1917 (Anura, Ptychadenidae) - Jacobo Reyes-Velasco (Pensoft Publishers, 2021)
The taxonomy of the Ptychadena neumanni species complex, a radiation of grass frogs inhabiting the Ethiopian highlands, has puzzled scientists for decades because of the morphological resemblance among its members. Whilst molecular phylogenetic methods allowed the discovery of several species in recent years, assigning pre-existing and new names to clades was challenged by the unavailability of molecular data for century-old type specimens. We used Illumina short reads to sequence the mitochondrial DNA of type specimens in this group, as well as ddRAD-seq analyses to resolve taxonomic uncertainties surrounding the P. neumanni species complex. The phylogenetic reconstruction revealed recurrent confusion between Ptychadena erlangeri (Ahl, 1924) and P. neumanni (Ahl, 1924) in the literature. The phylogeny also established that P. largeni Perret, 1994 represents a junior synonym of P. erlangeri (Ahl, 1924) and distinguished between two small species, P. nana Perret, 1994, restricted to the Arussi Plateau, and P. robeensis Goutte, Reyes-Velasco, Freilich, Kassie & Boissinot, 2021, which inhabits the Bale Mountains. The phylogenetic analyses of mitochondrial DNA from type specimens also corroborate the validity of seven recently described species within the group. Our study shows how modern molecular tools applied to historical type specimens can help resolve long-standing taxonomic issues in cryptic species complexes.